Gram-negative bacterial colonization in the gut: Isolation, characterization, and identification of resistance mechanisms - Yara Khachab; Said El Shamieh; Elie Salem Sokhn (Elsevier, 2024)
Background: The gut microbiome is made up of a diverse range of bacteria, especially gram-negative bacteria, and is crucial for human health and illness. There is a great deal of interest in the dynamic interactions between gram-negative bacteria and their host environment, especially considering antibiotic resistance. This work aims to isolate gram-negative bacteria that exist in the gut, identify their species, and use resistance-associated gene analysis to define their resistance mechanisms. Methods: Samples were collected from all patients who had a stool culture at a tertiary care center in Lebanon. Each type of bacteria that was identified from the stool samples was subjected to critical evaluations, and all discovered strains underwent antimicrobial susceptibility testing. Polymerase chain reaction was used to profile the genes for Carbapenem-resistant Enterobacteriaceae (CRE), Extended-spectrum beta-lactamase (ESBL), and that of Pseudomonas aeruginosa strains. Results: Escherichia coli, Klebsiella species, and Pseudomonas aeruginosa turned out to be the predominant microbiota members. Escherichia coli strains had a high frequency of extended-spectrum beta-lactamase genes, with the most discovered gene being bla CTX-M. Additionally, a considerable percentage of isolates had carbapenemase-resistant Enterobacteriaceae genes, suggesting the rise of multidrug-resistant strains. Multidrug resistance genes, such as bla mexR, bla mexB, and bla mexA, were found in strains of Pseudomonas aeruginosa, highlighting the possible difficulties in treating infections brought on by these bacteria. Conclusion: The findings highlight the critical importance of effective surveillance and response measures to maintain the effectiveness of antibiotics considering the introduction of multidrug resistance genes in Pseudomonas aeruginosa and ESBL and CRE genes in Escherichia coli.